Beyond numbers: integrating qualitative analysis into quantitative sensory testing for neuropathic pain - Bordeleau, Martine; Vincenot, Matthieu; Bačkonja, Miroslav; Cruz-Almeida, Yenisel; Forstenpointner, Julia; Gauthier, Lynn; Marchand, Serge; Mercier, Catherine; Ocay, Don Daniel; PrudHomme, Michel; Ruel, Hélène; Vollert, Jan; et al. (Frontiers in Pain Research, 2024)
This article investigates the benefits of adopting qualitative and quantitative sensory testing (QQST) in sensory assessment, with a focus on understanding neuropathic pain. The innovative QQST method combines participant qualitative experiences with quantitative psychophysical measurements, offering a more varied interpretation of sensory abnormalities and normal sensory function. This article also explores the steps for the optimization of the method by identifying qualitative signs of sensory abnormalities and standardizing data collection. By leveraging the inherent subjectivity in the test design and participant responses, the QQST method contributes to a more holistic exploration of both normal and abnormal sensory experiences. This article positions the QQST approach as a foundational element within the Sensory Evaluation Network, uniting international experts to harmonize qualitative and quantitative sensory evaluation methods.